The Influence of Learning Motivation on Students’ Achievement in Learning Indonesia - Yuni Pertiwi; Sukarno Sukarno; Vebbi Andra (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This research is motivated by the phenomenon that all parents want their children's education to be good, so they pay attention and optimize for their children's education. The existence of this need, humans are encouraged to fulfill it. This encouragement is called motivation. In this case, of course the role of motivation is very important. The objectives of this study are (1) to determine whether there is an effect of learning motivation on student learning achievement at SMPN 1 Bengkulu city. (2) To determine how much significance the effect of student learning motivation on student learning achievement in SMPN 1 Bengkulu city.This study uses a quantitative approach with regression type.The population is SMMPN 1 Bengkulu city which totals 854 students. The sample was 90 students, the method of data research with questionnaires and documentation. All instruments have met the measurement requirements, because they have been tested so that they have met the validity test requirements using product correlation and reliability using Cronbach alpha, and have passed the prerequisite test. Data analysis using the T test and the percentage of influence using the coefficient of determination adjuster Rsquare. The results showed that (1) there is a significant effect of learning motivation on learning achievement as evidenced by the value of Rhitung> Rtabel, namely 0.611> 0.361 and Sig <0.05, namely 0.000 <0.05. (2) The effect of the coefficient of determination Adjusted R square 0.020 on the summary model in the regression test, so that the effect of learning motivation (X), on learning achievement (Y) is 2%.